Combining Total Cost of Ownership and Integer Programming for 3PL Order Allocation in PT. X - Alexander Evan Putra; Ratih Dyah Kusumastuti (Eduvest - Journal of Universal Studies, 2025)
Managing multiple third-party logistics providers (3PLs) for export shipments presents a complex challenge for large manufacturers like PT. X, involving both explicit and implicit costs that impact overall efficiency and cost-effectiveness. This study aims to develop an optimal 3PL order allocation model for PT. X's export operations by integrating Total Cost of Ownership (TCO) to capture comprehensive costs and Integer Programming (IP) to minimize these total costs. A case study approach was employed, utilizing data from PT. X, including 3PL quotations, operational records, and quality performance metrics. The TCO framework incorporated both explicit costs (e.g., shipment and service fees) and implicit costs (e.g., management and quality failures). An IP model was then formulated to allocate orders across five 3PLs while adhering to operational constraints on minimum and maximum volumes per 3PL and shipping liner. The combined TCO-IP model achieved a cost saving of Rp 1.52 billion (4.57%) compared to PT. X's previous allocation method. Sensitivity analysis revealed that implicit costs (communication and quality), while captured by TCO, had an insignificant impact on the overall allocation due to their small proportion in the total cost structure. The research demonstrates the practical value of combining TCO and IP for strategic logistics decision-making, enabling significant cost savings. It suggests that for PT. X, minimizing explicit costs is the primary driver of optimal 3PL allocation, though monitoring implicit costs remains important.